(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Sero-epidemiological study were conducted for pregnant and aborted women to investigate the infection person with toxoplasmosis in Babylon province during the period from December 2018 till March 2019 ,ELISA technique for 53 serum samples for pregnant and 67 serum sample for aborted women , according to epidemiological criteria (Residence area , age group , existence of cats in houses , times number of abortion status , number of children , collection samples monthly, trimesters period of pregnancy). Concerning biochemical parameters, the present included determination of estradiol hormone and vascular cell adhesion molecule -1(VCAM-1) in aborted and healthy women that their ages ranged between 20 to 49 years old. it has been found a significant increase (P<0.05) in the levels of estradiol hormone in women affected with toxoplasmosis compared to healthy women .VCAM-1 results indicated a significant increase(P<0.05) in a comparison with those of healthy women it can be concluded that infection with Toxoplasma gondii is associated with estradiol hormone and vascular cell adhesion molecules.